Psychotherapy of Professional Addictions in the Context of EU Compass for Mental Health Policy in Organizations - Zasiekina, Larysa (Psychological Prospects Journal, 2018)
The problem of professional addictions in general and workaholism in part as destructive factor for mental health in organizations is highlighted in the article. The contradictions in the definition of workaholism are underlined. The workaholism contains the positive aspects as high material and social status, high achievements, national wealth and negative aspects: poor physical and mental health, low level of wellbeing and quality of life. The most widespread criteria are the amount of time, spent for a work, attitude to it, extra investments to the work performance, and obsessions over work all time. The main typology of workaholismis defined. Among the main types there are compulsive-dependant, achievements-oriented, perfectionists; bulimic, relentless, attention-deficit, savoring; with and without enthusiasm and satisfaction. The main mechanisms of workaholism and its typology is the concentration on the work itself and its content or on the act of working. The main spheres for risk of workaholismare defined, among them there are state officers. The results of the empirical research of state officials in Volyn oblast show that 28,6 % among them have symptoms of workaholism and demand psychoeducative and therapeutic help. The lower indices of different scales of quality of life: family, social support, spiritual needs and comfort, health in persons with the workaholism symptoms were revealed. The EU policy in mental health improvement and promotion is analyzed and its implementation in Ukrainian organizations is suggested.